Existência e escritura em Cioran - Menezes, Rodrigo Inácio Ribeiro Sá (2016)
Cioran (1911-1995) is a Romanian-French thinker who would not have the right to complain about being misunderstood or even ignored, inasmuch as he begged to turn marginality into a philosophical imperative and a lifestyle. Eleven years since his death, in Paris, and one hundred since his birth, in Transylvania, this one author, the perfect stranger in more than one sense, remains largely unknown by the Brazilian audience, scholarly or not, in such a way that his shady aura, so to speak, as well as countless legends and rumors prevail about his life, personality and thought. Having said that, and apart from his own will to marginality, Cioran is a thinker who just can t and will not remain as such for much longer ignored or spurned, be it by Academia as such or by particular intellectual milieus with varied ideological outlooks. All the more when it comes to reflect upon problems which happen to be just as prevailing as worrying, such as the rise of integralism and of fanaticism, be it religious or of any other kind, atheism, skepticism and nihilism in the XXth century, anguish, despair, the metaphysical need of mankind and the sense of ultimate transcendence, suffering, death, suicide, evil, finally, a wide range of questions which are all highly relevant from a philosophical standpoint and also that of human sciences. In the first part of this inquiry, we aim at showing that philosophical pessimism and apophatic dwell mix up in the existential metaphysics of Cioran, a religious philosophy of existence which, not being guided up by the faith in revealed truths and by the adhesion to external authorities, aims to think human existence and condition according to that which is most imperious and essential, in Cioran s view, when it comes to the metaphysical animal: wisdom rather than science, deliverance by disillusion rather than salvation by faith and knowledge, the need for the absolute to the detriment of the delusions of becoming, coping with the contingency inherent to existence, namely human existence, tragically gifted with reflexive consciousness, freedom, a destiny. Cioran s organically existential thought is inseparable from, as he puts it, from his own life experience, namely the insomnia to which he accredits the merit or the fault for his blessed, for his cursed lucidity: a state of mind incompatible with life, turning life into a state of non-suicide . If there is pessimism, skepticism, nihilism, mysticism within the sum of attitudes that composes the works of Cioran, such attitudes which might as well be modalized as reactions to the problem of evil, all these tendencies emanate from insomnia-bred lucidity. Secondly, we shall turn our attention to the topic of Cioran s écriture, with everything it implies, differently than his Romanian writing, as far as style, concern for expression and the aestheticizing of discourse are concerned. We aim at showing that the Farewell to philosophy enounced by the author in A short history of decay (Précis de decomposition), parallel to his literary turn and the radicalization of the fragmentary principle that precedes his French writing, is the paradoxical expression of a negation-driven thought which, by betraying Philosophy with Poetry, Music and Mysticism, cannot help but pay an unheard-of tribute to Human thought and to Philosophy itself. Finally, we argue that Cioran s French works represent, by its form and content, the necessary consequence and exact expression of a lucid, organic thought, which discovers in the écriture de soi the very destiny of Western Philosophy, and in Style as adventure the highest form of modern-thought heroism